PELAYANAN KESEHATAN PADA LANSIA DI KELURAHAN MAPANGET BARAT LINGKUNGAN VIII KOTA MANADO: HEALTH SERVICES FOR ELDERLY AT KELURAHAN MAPANGET BARAT LINGKUNGAN VIII - Ningrum, Puspita; Woran, Develin; Onibala, Franly; Rondonuwu , Junytha; Purwanti5, Erna; Parapaga, Noviyanti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2025)
The fact that the number of elderly people is increasing shows how difficult the disease is. The number of deaths worldwide reached 56.9 million in 2016, 71% of which were caused by non-communicable diseases (NCDs). The World Health Organization issued a Global Action Strategy to combat NCDs, which includes increasing public and political awareness, understanding and practice of prevention, and control of NCDs. This strategy is implemented through health education, psychological interventions such as cognitive behavioral therapy and motivational interviewing, and routine checks of public health services. The purpose of writing this article is to inform people, especially older people, about the dangers of diseases such as diabetes, stroke, heart disease, arthritis due to gout, and others. This community service was carried out in Mapanget Barat Village, Environment VIII with a total of 34 elderly people. Examination and exercise were the methods used. The results and discussions produced showed that the majority of elderly people had high blood pressure uric acid, while cholesterol was only 7 elderly people out of a total of 34 elderly people, while blood sugar of half of the elderly was detected as high and some were normal.